1992
DOI: 10.1021/jm00080a005
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and opioid activity of analogs of the analgesic dipeptide 2,6-dimethyl-L-tyrosyl-N-(3-phenylpropyl)-D-alaninamide

Abstract: A number of analogues of the recently disclosed analgesic dipeptide 2,6-dimethyl-L-tyrosyl-D-alanine-phenylpropylamide (SC-39566, 2) were prepared. These analogues contained oxymethylene, aminomethylene, ketomethylene, bismethylene, and trans double bond (including vinyl fluoride) isosteric replacements for the amide bond between the D-alanine and phenylpropylamine units in 2. These compounds were tested in opioid binding assays and in the mouse writhing assay for analgesic activity. Though not as potent as 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 2 publications
0
25
0
Order By: Relevance
“…Although a number of high-yielding procedures are available for the selective acylation of simple a-or b-aminoalcohols, [13] literature reports on the selective acylation of a,b-diaminoalcohols are scarce. [14] Initial attempts to couple 1 with the substituted cinnamic acid 3'-cyano-6'-methoxycinnamic acid in the presence of several activating agents such as acid chlorides, carbodiimides, or uronium and phosphonium reagents, delivered low yields. The reaction outcomes were complicated by the presence of significant amounts of N,O-diacylated by-product.…”
Section: Proton-mediated Chemoselectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Although a number of high-yielding procedures are available for the selective acylation of simple a-or b-aminoalcohols, [13] literature reports on the selective acylation of a,b-diaminoalcohols are scarce. [14] Initial attempts to couple 1 with the substituted cinnamic acid 3'-cyano-6'-methoxycinnamic acid in the presence of several activating agents such as acid chlorides, carbodiimides, or uronium and phosphonium reagents, delivered low yields. The reaction outcomes were complicated by the presence of significant amounts of N,O-diacylated by-product.…”
Section: Proton-mediated Chemoselectivitymentioning
confidence: 99%
“…[22] In a marked improvement to synthetic efficiency, Enick, Hamilton, and co-workers showed that protection and deprotection can be circumvented by performing the reaction under acidic conditions. [23] In the presence of AcOH, the nucleophilicity of the amine is attenuated, thereby allowing the acylation of all five hydroxy groups of d-glucamine (14) to occur in one step, thus affording 15 in 72 % yield (Scheme 7).…”
Section: Proton-mediated Chemoselectivitymentioning
confidence: 99%
“…Recent structure-activity studies have shown that introduction of the artificial amino acid 2Ј,6Ј-dimethyltyrosine (Dmt) in place of the N-terminal Tyr residue is a promising way to greatly enhance receptor affinity and functional potency. [2][3][4][5][6][7][8][9][10][11][12][13] However the Dmt 1 -substitution generally has resulted in low receptor selectivity due to markedly enhanced affinity toward the concomitant receptor vs. the preferred receptor. 3,6,8,12,13) We have recently demonstrated that 2Ј,6Ј-dimethylphenylalanine (Dmp) is an excellent surrogate for the Phe at position 3 in Tyr-D-Arg-Phe-bAla-NH 2 (YRFB), 14) endomorphin 2, 15) dermorphin, 16) and deltorphin II.…”
mentioning
confidence: 99%
“…The effectiveness of Dmt to modify peptide behavior was demonstrated by the drastic increases in δ-or µ-receptor affinity. Substitutions of Dmt in place of Tyr at the N-terminus of diverse groups of opioid peptides produced a broad range of activities [87][88][89][90][91][92]. A δ-agonist deltorphin-II 81 acquired high µ-bioactivity [93], while the κ-agonist dynorphin(1-11)NH 2 became a κ-antagonist 83 [94].…”
Section: Methylation Of the Aromatic Rings Of Tyrosine And Phenylalaninementioning
confidence: 99%